(untitled) - Rostow, W. W. (New York, 1975)
Rostow traces the origins of the modern economy seeking to explain the routes by which nations achieve wealth or have become impoverished. 264 pages with index.
Keywords: Economic history,Economic history,Lịch sử kinh tế,Lịch sử kinh tế; 1600-1750,1750-1918,1600-1750,1750-1918